The study on factors influencing the quality perceptions of dairy products among schools teachers in Ranau / Mohd Farid Mohd Zaini - Mohd Zaini, Mohd Farid (2014)
People are becoming more health awareness nowadays due to development in educational and technology advancement influencing also towards the consumption of food among peoples from traditional food consumption to more healthier consumption; as can be seen among Malaysian trend for breakfast had change from traditional breakfast consists of fried rice, fried noodles and etc. to more healthier breakfast such as bread, milk, dairy products and etc. The health benefits of dairy product are become more acknowledged to people as the consumption for dairy products are increasing. This research will study on the factors influencing the quality perceptions of dairy products among schools teachers in Ranau. By utilizing the aid of questionnaire, distributed to the target sample, the objectives of this research is to determine the purchasing pattern of dairy products among teachers in Ranau, examine the factors lead to quality perceptions on dairy products among schools teachers in Ranau and determining the significance influence of three identified factors (price, brand acknowledgement and packaging information) towards quality perceptions of dairy products. Analysis on percentage and frequency distribution are conducted for nominal variables. Pearson Correlation Coefficient as to determine the correlation between each independent variables toward the dependent variables and Multiple Regression Analysis as to determine the p-value or significance of each independent variables toward the dependent variable as well as to determine the percentage of those independent variables in explaining the dependent variable through calculations of R2. Results shows that all three factors analyzed (price, brand and packaging information) do have significant influence towards perceived quality of dairy products among school teachers in Ranau. However, packaging information and brand has more significance influence compared to price towards the perceived value of dairy products among school teachers in Ranau. The result of the study will be a leading paradigm in the related firms whereby this research will provide related firms with a better concept of factors affecting the demand and purchasing pattern among working personnel, thus, coming out with proper planning in the future for effective marketing strategies, therefore, ensuring consumer satisfaction.